Single‐wall and multi‐wall carbon nanotubes promote rice root growth by eliciting the similar molecular pathways and epigenetic regulation. Issue 4 (1st August 2016) - Yan, Shihan; Zhang, Hao; Huang, Yan; Tan, Junjun; Wang, Pu; Wang, Yapei; Hou, Haoli; Huang, Jin; Li, Lijia
Abstract : Organisms are constantly exposed to environmental stimuli and have evolved mechanisms of protection and adaptation. Various effects of nanoparticles (NPs) on crops have been described and some results confirm that NPs could enhance plant growth at the physiological and genetic levels. This study comparatively analysed the effect of carbon nanotubes (CNTs) on rice growth. The results showed that single‐wall CNTs were located in the intercellular space while multi‐wall CNTs penetrated cell walls in roots. CNTs could promote rice root growth through the regulation of expression of the root growth related genes and elevated global histone acetylation in rice root meristem zones. These responses were returned to normal levels after CNTs were removed from medium. CNTs caused the similar histone acetylation and methylation statuses across the local promoter region of the Cullin‐RING ligases 1 (CRL1) gene and increased micrococcal nuclease accessibility of this region, which enhanced this gene expression. The authors results suggested that CNTs could cause plant responses at the cellular, genetic, and epigenetic levels and these responses were independent on interaction modes between root cells and CNTs.